Indikator Dominan pada Perilaku Kompulsif Remaja dalam Mengakses Internet - Nurmalasari, Yuli (Universitas Negeri Semarang, 2020)
Perilaku kompulsif dalam mengakses internet merupakan tahap ‘transisi’ yang memiliki karakteristik psikologis yang berbeda. Tujuan penelitian mengidentifikasi indikator dominan pada perilaku kompulsif remaja dalam mengakses internet. Penelitian menggunakan metode deskriptif kualitatif terhadap 103 siswa sekolah menengah pertama. Hasil penelitian menunjukkan indikator dominan dalam perilaku kompulsif mengakses internet adalah kehilangan kendali diri, indikasi menarik diri, dan fungsi mengatasi ketidaknyamanan psikologi melalui pengaksesan internet. Kata kunci:perilaku kompulsif, internet, online, media sosial Compulsive behavior in accessing the internet is closely related to the duration and frequency of accessing the internet, as well as more describing the characteristics of using uncontrolled internet applications rather than pathological addictions. The purpose of the study is to identify dominant indicators of adolescent compulsive behavior in accessing the internet. The study used a qualitative descriptive method with random sampling techniques to 103 junior high school students. Compulsive behavior in internet use is measured by a modification of the Compulsive Internet Use Scale (CIUS) instrument designed by Meerkerk et al (2007). The results showed three dominant indicators that indicate the level of compulsivity consisted of loss of control related to loss of self-control; withdrawal symptom which is an indication of withdrawing through the internet; and coping, the function of overcoming psychological discomfort through the internet access.